Adjuvant Effect of Bacille Calmette–Guérin on Hepatitis B Vaccine Immunogenicity in the Preterm and Term Newborn - Scheid, Annette; Borriello, Francesco; Pietrasanta, Carlo; Christou, Helen; Diray-Arce, Joann; Pettengill, Matthew A.; Joshi, Sweta; Li, Ning; Bergelson, Ilana; Kollmann, Tobias; Dowling, David J.; Levy, Ofer (Frontiers in Immunology, 2018)
Immunization is key to protecting term and preterm infants from a heightened risk of infection. However, preterm immunity is distinct from that of the term, limiting its ability to effectively respond to vaccines routinely given at birth, such as hepatitis B vaccine (HBV). As part of the Expanded Program on Immunization, HBV is often given together with the live attenuated vaccine Bacille Calmette-Guérin (BCG), known to activate multiple pattern recognition receptors. Of note, some clinical studies suggest BCG can enhance efficacy of other vaccines in term newborns. However, little is known about whether BCG can shape Th-polarizing cytokine responses to HBV nor the age-dependency of such effects, including whether they may extend to the preterm. To characterize the effects of BCG on HBV immunogenicity, we studied individual and combined administration of these vaccines to cord newborn and adult human whole blood and mononuclear cells in vitro and to neonatal and adult mice in vivo. Compared to either BCG or HBV alone, (BCG+HBV) synergistically enhanced in vitro whole blood production of IL-1beta. While (BCG+HBV) also promoted production of several cytokines/chemokines in all age groups, age-specific enhancement included IL-12p70 in the preterm and GM-CSF in the preterm and term. In human mononuclear cells, (BCG+HBV) enhanced mRNA expression of several genes including CSF2, which contributed to clustering of genes by vaccine treatment via principle component analysis. To assess the impact of BCG on HBV immunization, mice of three different age groups were immunized subcutaneously with, BCG, HBV, (BCG+HBV) into the same site; or BCG and HBV injected into separate sites. Whether injected into a separate site or at the same site, co-administration of BCG with HBV significantly enhanced anti-HBV IgG titers in mice immunized on Day of Life (DOL)-0 or -7 respectively, but not in adult mice. In summary, our data demonstrate that innate and adaptive vaccine responses of preterm and term newborns are immunologically distinct. Furthermore, BCG or “BCG-like” adjuvants should be further studied as a promising adjuvantation approach to enhance immunogenicity of vaccines to protect these vulnerable populations.